A synthetic biofilter media for ammonia (NH3) removal - Shareefdeen, Zarook (2012)
In this work, a patented biofilter media is used in treating air contaminated with ammonia (NH3). The data shows up to 200 ppm of NH3 can be removed with over 93% removal efficiency at 30 s Empty Bed Residence Time (EBRT). At the start-up conditions, the results also indicated that the humidifier can be utilised for buffering concentration fluctuations. The design correlation developed based on the zero-order model can be used as a preliminary estimate for sizing biofilters for NH3 removal. The results show that predictions using the design correlation are in good agreement with the experimental data.